Al-Fātiḥahas Spiritual Therapy: A Study of the Qur’an sPsychological Miracle - Khomsa maulana (DAAR EL-KAMIL: Multidisciplinary Journal, 2025)
Surah al-Fātiḥah, known as the Umm al-Qur’ ān (the Motherof the Qur’an), holds aunique position not only theologically but also psychologically. Fromthe perspective of i‘ jāz nafsī,al-Fātiḥah demonstratesspiritualmiracles thattouch thesoul, bring inner peace, and strengthen human psychological resilience. This article aims to examine the psychological dimensions of al-Fātiḥah through classical and contemporary exegesis, aswell as modern psychological approaches. The method used is a literature review with descriptive-qualitative analysis, connecting Qur’anic textswith conceptsof religiouspsychology.The findingsreveal that theseven verses of al-Fātiḥah function as spiritual therapy by nurturing gratitude, hope, faith, and self-control. Itsrepetition in daily prayers acts as a form of spiritual conditioning that supports both individual and collective mental health.Thus, al-Fātiḥah remains relevantas a sourceofinner peace and psychological therapy across generations.